2010
DOI: 10.1021/jp1088299
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Excited State Distortions in a Pyrazolate Bridged Platinum Dimer Measured by X-ray Transient Absorption Spectroscopy

Abstract: The excited-state structure of a dinuclear platinum(II) complex with tert-butyl substituted pyrazolate bridging units, [Pt(ppy)(μ-(t)Bu(2)pz)](2) (ppy = 2-phenylpyridine; (t)Bu(2)pz = 3,5-di-tert-butylpyrazolate) is studied by X-ray transient absorption (XTA) spectroscopy to reveal the transient electronic and nuclear geometry. DFT calculations predict that the lowest energy triplet excited state, assigned to a metal-metal-to-ligand charge transfer (MMLCT) transition, has a contraction in the Pt-Pt distance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 51 publications
12
99
1
2
Order By: Relevance
“…This was followed by a ps XAS study on another diplatinum comple by Chen and co-workers, 223 who also showed bond formation in the excited state with a contraction of the Pt-Pt distance by ~ 0.2 Å.…”
Section: Bond Forming Dynamicsmentioning
confidence: 87%
“…This was followed by a ps XAS study on another diplatinum comple by Chen and co-workers, 223 who also showed bond formation in the excited state with a contraction of the Pt-Pt distance by ~ 0.2 Å.…”
Section: Bond Forming Dynamicsmentioning
confidence: 87%
“…40 This has provided an efficient method of acquisition on a time scale of 100s ns to 1 μs with a time resolution of 100 ps. By using an optimized laser repetition rate for the SLS (520 kHz), transient XAFS of MbCO (2 mM) have been obtained in ∼4.5 h. 41 The principal disadvantage of the dispersive approach is the restriction to a transmission geometry and thus this test experiment utilized relatively high concentrations (15–20 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TR-XAS spectroscopy has been employed to study the structural distortions in the triplet ESs of two binuclear Pt-complexes, i.e. the Pt-POP system (see also §4d) [159] and the [Pt(ppy)(µ− t Bu 2 pz)] 2 (ppy = 2-phenylpyridine; t Bu 2 pz = 3,5-di-tert-butylpyrazolate) complex [248]. Several studies concerned the structural dynamics of photodissociated intermediates in the solution phase as in the case of NiTPP-L 2 and NiTMP (where TPP = nickel tetraphenylporphyrin, L = piperidine and TMP = tetramesitylporphyrin) [249,250].…”
Section: (Py) 2 ] 2+mentioning
confidence: 99%